Factors Associated With Burnout Among Nurses Providing Direct Patient Care During the COVID-19 Pandemic. (November 2022) - Cohen, Bevin; DePierro, Jonathan; Chan, Chi C.; Tolan, Elaine; Deshpande, Richa; Feder, Adriana; Feingold, Jordyn H.; Peccoralo, Lauren; Pietrzak, Robert H.; Ripp, Jonathan
Abstract : OBJECTIVE: This study aimed to identify factors associated with burnout in nurses and nurses' opinions regarding interventions to promote well-being during crisis conditions such as those experienced during the COVID-19 pandemic. BACKGROUND: Burnout among nurses is prevalent under usual conditions and may increase during crises such as COVID-19. METHODS: Researchers conducted a survey of 1103 frontline nurses in a single New York City hospital during the first (spring 2020) and second (fall 2020/winter 2021) local waves of COVID-19. RESULTS: Burnout prevalence increased from 45% to 52% between the first and second wave. Younger age, female gender, posttraumatic stress, anxiety or depressive symptoms, history of burnout, feeling less valued by hospital leadership, less informed of responsibilities, less certain about duration of enhanced workload, and prepared by prepandemic experience were predictive of burnout in multivariable analyses. CONCLUSIONS: Although some identified risk factors for burnout were nonmodifiable, others may be modifiable by hospital leadership.